High percentages of larval tetraploids in the yellowtail tetra Astyanax altiparanae induced by heat-shock: The first case in Neotropical characins - Nascimento, Nivaldo Ferreira do [UNESP]; Pereira-Santos, Matheus [UNESP]; Levy-Pereira, Nycolas; Monzani, Paulo Sergio; Niedzielski, Daiane; Fujimoto, Takafumi; Senhorini, Jose Augusto; Okada Nakaghi, Laura Satiko [UNESP]; Yasui, George Shigueki (Elsevier B.V., 2020)
Tetraploid fish are an important source of diploid gametes for polyploid production, and they can be induced by inhibition of the first mitotic cell division. Dispite its potential, very few protocols regarding tetraploidization and subsequent application to mass production of triploid fish for aquaculture exist. In the yellowtail tetra Astyanax altiparanae, triploids present sterility and increased carcass yield, suggesting the generation of tetraploid for large-scale production of such triploids. In this study, the efficacy of heat shock treatments (40 degrees for 2 min) at 16, 18, 20, 22, 24, and 26 min post-fertilization (mpf) at an incubation temperature of 22 degrees C were compared on tetraploid induction of A. altiparanae. Ploidy status was confirmed by flow cytometry, karyotyping, and nuclear diameter of erythrocytes. Afterwards, sperm parameters and fertility capacity of tetraploid males were evaluated. The results showed that heat shock decreased the hatching rate, especially at 22 (19.1 +/- 9.6%), 24 (16.0 +/- 9.1%), and 26 mpf (10.3 +/- 6.2%) in comparison with the control group (62.2 +/- 7.7%). The flow cytometric analysis showed that the control group and the treatments with heat shock at 16 and 18 mpf presented only diploid individuals. However, from 20 mpf onwards, tetraploid individuals were observed, and the highest percentage arose at 26 mpf (94.55%). When mature, tetraploid males are capable of producing diploid spermatozoa with fertilization capacity, generating a 100% triploid offspring. The results indicate that the heat shock treatment at 26 mpf (40 degrees C for 2 min) is optimum for tetraploid induction in the A. altiparanae. Additionally, tetraploid mature males generated diploid spermatozoa and can be used to mass production of triploid fish. The current data are the first report of tetraploids in family Characidae, presenting an application in basic and applied sciences.
Keywords: Fish; Chromosome manipulation; Heat-shock; Polyploidy